2022
DOI: 10.3389/fnut.2022.807634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Retinol Concentrations With Metabolic Syndrome Components in Iranian Children and Adolescents: The CASPIAN-V Study

Abstract: BackgroundAs a fat-soluble vitamin, vitamin A plays a crucial role in adipogenesis, lipolysis, insulin resistance, and obesity. However, it is still unclear whether they are associated with cardiometabolic risk factors in children and adolescents. The current study aimed to determine the association between serum retinol concentration and the cluster of metabolic syndrome components among children and adolescents.MethodsThis nationwide cross-sectional study was performed on 2,518 students aged 7–18 years from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Moreover, trans-β-carotene, as a provitamin A, could decrease children’s body mass index (BMI), truncal fat mass, and total body fat mass, while vitamin A exhibited the opposite effects ( 58 ). Studies have indicated that increasing serum retinol level is positively associated with a higher prevalence of obesity and other metabolic indicators, including lower HDL-C and higher fasting blood glucose levels ( 59 , 60 ). Moreover, in this study, the Qgcomp and RCS models showed that vitamin A was positively associated with the risk of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, trans-β-carotene, as a provitamin A, could decrease children’s body mass index (BMI), truncal fat mass, and total body fat mass, while vitamin A exhibited the opposite effects ( 58 ). Studies have indicated that increasing serum retinol level is positively associated with a higher prevalence of obesity and other metabolic indicators, including lower HDL-C and higher fasting blood glucose levels ( 59 , 60 ). Moreover, in this study, the Qgcomp and RCS models showed that vitamin A was positively associated with the risk of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Qorbani et al also found that retinol concentration was positively associated with metabolic syndrome components, such as obesity, low HDL, and high FBG levels. They also indicated that vitamin A level and its association with metabolic response is influenced by some genetic variations [ 46 ]. We did not observe any significant correlation between vitamin A and thyroid function parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that the effect of these factors on retinol levels does not necessarily reflect a good vit-A status, but merely that the body's retinol stores have been redistributed from the liver into circulation [ 37 ]. Meanwhile, an inadequate intake of vit-A for four months can lead to the depletion of retinol stores in the liver [ 38 ] and generate a deficiency in serum levels, as evidenced in adolescents in Brazil [ 39 ], China [ 40 ], the Philippines [ 41 ], Iran [ 42 ], and India [ 43 ]. Although it has been suggested that vit-A deficiency is manifested primarily as a subclinical disease in the Americas [ 44 ], it could generate deleterious effects on the health of adolescents through different pathways, such as those mentioned in the introduction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%